Awareness and Perception of Consumers on Motor Insurance in Kathmandu Valley - Tandukar, Pragika (Nepalese Journal of Finance, 2025)
This study examines the awareness and perception of consumers on motor insurance in Kathmandu Valley. Perception of consumers is the dependent variable. The selected independent variables are premium rate, service quality, experience, company image and security. The primary sources of data is used to assess the opinions of respondents regarding premium rates, service quality, experience, company image, security and perception of consumers. The study is based on the primary data of 128 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of awareness and perception of consumers on motor insurance in Kathmandu Valley. The study showed a positive impact of premium rates on perception of consumers. It indicates that affordable premium rates leads to have positive perception of consumer towards motor insurance product. Similarly, the study showed a positive impact of service quality on perception of consumers. It indicates that higher the service quality, higher would be the perception of consumer. Likewise, the study showed a positive impact of experience on perception of consumers. It indicates that individuals who have more exposure or interaction with a product or service tend to form more favorable opinions to motor insurance product. Further, the study showed a positive impact of company image on perception of consumers. It indicates that higher the reputation of a company leads to change in the perception of consumers. In addition, the study showed a positive impact of security on perception of consumes. It indicates that enhancing security measures leads to enhance the perception of consumer.